The Poetics of Cavafy : Textuality, Eroticism, History - Jusdanis, Gregory, 1955- (Book collections on Project MUSE., 1987)
This full-length theoretical examination of Constantine Cavafy breaks the study of this great Greek poet free from the narrow context of traditional scholarship and introduces the latest critical developments into the study of Greek poetry. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.